Building Speaking Confidence Through English Competitions: Non-English Department Students' Lived Experiences - Zahra Kamilah Ramadhani; Nova Lingga Pitaloka (International Journal of Education Research and Development, 2026)
Confidence in speaking is a crucial aspect of English communication, particularly for non-English major students who often struggle to express themselves. This study aimed to understand the lived experiences of non-English major students in developing their speaking confidence through participation in English competitions. This study employed a qualitative approach involving several participants who had experience in participating in oral English competitions. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify key patterns and themes. The findings showed that participants initially had low levels of speaking confidence, which were influenced by factors such as fear of making mistakes, limited vocabulary, and concern about pronunciation. However, their confidence gradually improved through repeated participation in English competitions. In addition, English competitions shaped students’ speaking confidence by providing a supportive learning environment, real-life speaking experiences and opportunities to receive feedback. These findings indicated that English language competitions played a significant role in supporting the development of speaking confidence among non-English-major students.